Welcome to dead house - Stine, R. L. (New York : Scholastic, 1992)
After moving to the town of Dark Falls and finding their new--old--house very creepy, Amanda and Josh's parents encourage them to make new friends, which proves to be a hauntingly dangerous mistake.
4.6
5-8
Keywords: Moving, Household -- Juvenile fiction; Ghosts -- Fiction; Horror stories; Moving, Household -- Fiction; Ghost stories; Horror fiction; Moving -- Fiction; Ghost stories; Horror fiction